Autophagy and Mechanisms of Effective Immunity - Mintern, Justine; Villadangos, Jose A. (Frontiers in Immunology, 2012)
Macroautophagy (autophagy) is a cellular pathway facilitating several critical functions. First, autophagy is a major pathway of degradation. It enables elimination of microbes that have invaded intracellular compartments. In addition, it promotes degradation of damaged cellular content, thereby acting to limit inflammatory signals. Second, autophagy is a major trafficking pathway, shuttling content between the cytosol and the lysosomal compartment. Given these two key roles, autophagy can have significant and sometimes unexpected consequences on mechanisms that initiate robust immunity. Here, we will discuss the impact of autophagy on pathways of innate and adaptive immune responses including microbe elimination, inflammatory cytokine production, antigen processing and T and B lymphocyte immunity.